Sistem Informasi Akademik Berbasis Cloud pada Akademi Farmasi Mandiri Banda Aceh - Ismail, Ismail; Harmisal, Harmisal; Jumaidin, T Faisal (KITA Institut, 2018)
Cloud-based academic information system at Academy of Pharmacy Mandiri Banda Aceh is an application system used to do processing of academic data at Academy of Pharmacy Mandiri Banda Aceh with the use of cloud computing services as an academic information system infrastructure. The problem discussed is how to make information system in giving fast and correct report at Mandiri Banda Aceh Pharmacy Academy. The purpose of this study is to analyze the needs of Academic data information at the Academy of Pharmacy Mandiri Banda Aceh, because during this processing of data lectures are still using office applications and not use cloud technology, so the resulting information is ineffective and takes a very long time and cause effects data inaccuracies. During the execution of the last task carried out assessment of the problem and the basic theory of lecture data so that the system needs specifications to solve the problem by the basic theory that has been studied. Furthermore, an information system design is done, including system development method used to build an information system covering the steps of analysis, design, and implementation. From the discussion that the author did, in get the conclusion that the data processing can be developed further by utilizing Lazarus IDE and cloud technology.